Structural performance of RC beams strengthened with NSM (soffit and side) / Md. Akter Hosen - Md. Akter, Hosen (2015)
RC structures around the world require rehabilitation or strengthening for various reasons, such as increased load, the repair of damaged members, modification of the structural system, improvement of the structure, or errors in design and construction. In recent decades, strengthening has inevitably been a good choice in terms of structural efficacy as well as from an economic point of view. The near surface mounted (NSM) and the proposed side near surface mounted (SNSM) with steel or carbon fibre reinforced polymer (CFRP) bars provide suitable approaches for the enhancement of the flexural performance of RC beams. However, the NSM-steel technique has only been implemented in very few existing research, and, hence, is still an interesting issue. Furthermore, the SNSM approach to strengthening is a new concept. The main goal of this study is to investigate the experimental behaviour of RC rectangular beams strengthened using the NSM and newly developed SNSM techniques. To strengthen RC beams, CFRP composites (bars and fabric) and steel bars were used as the strengthening materials. Twenty-five (25) RC beams were fabricated for the experimental programme. The RC beams were cast in the concrete laboratory and divided into seven groups. The first group consisted of one unstrengthened beam as the control beam (CB) to represent the existing structural member. The other groups were strengthened by incorporating NSM, NSM with end anchorage (CFRP fabrics) and the proposed SNSM technique, with different configurations of CFRP and steel bars subjected to gradually increasing static load. All the representative RC beams were tested by a highly precise Instron Universal testing machine and the results were recorded using an automatic data logger. The experimental results showed that the ultimate capacity of the RC beams strengthened with NSM steel bars increased 96% more than the control beam. When the RC beams were strengthened using NSM steel bars and end anchorage using CFRP fabric, the ultimate capacity was enhanced by 132%. Moreover, a 93% and 138% increase in the ultimate capacity was achieved by strengthening the RC beams with SNSM steel and CFRP bars, respectively. An improvement of 130% in the ultimate capacity was achieved once the pre-cracked beams were strengthened with SNSM CFRP bars. An analytical model has been developed to predict the load, deflection and compressive strain in concrete; the tensile strain in the main reinforcement; and the strain in the NSM bars of the RC beams (control and strengthened) under static loading using sectional analysis. The flexural crack spacing of the RC beam specimens was predicted from existing models. The experimental results showed good agreement with the results obtained from the analytical models. It has been revealed that the deflection of the strengthened beams was significantly smaller than that of the unstrengthened beams. In addition, strengthening using the NSM and SNSM technique decreased the spacing of the cracks and increased the number of cracks. The crack widths also reduced with the increasing number of cracks.